Design, fabrication and Optical Characterization of Multi-Component Photonic Crystals for Integrated Si Microphotonics - PEROVA, TANIA (My University, 2011)
This paper reports on investigation and possible applications of the optical elements based on one-dimensional (1D) multi-component photonic crystal (PCs). The gap map approach and the transfer matrix method were used in order to mathematically describe multi-component 1D PC structures. We have found that the introduction of the additional regular layer into PC affects the properties of high-order PBGs, resulting in their vanishing in the certain range of the wavelengths and the formation of wide regions of total transparency instead. Tuning the number, position and width of these regions of total transparency in Si PCs has been demonstrated using the map of transmission bands. By analogy with multilayer dielectric coatings the additional component in multi-component Si PCs can be considered as an antireflection layer. The experimental results for the high-contrast multi-component PCs based on SiO2-Si-SiO2-Air structure with wide transmission bands are demonstrated in this study. The suggested approach can also be applied to the design of any micro- and nano- structured semiconductor or dielectric materials for application across wide electromagnetic spectrum.
Proceedings SPIE
Photonic West 2011
PUBLISHED
San Francisco
Keywords: Optics; 1D Photonic ?rystal; Nanoscience & Materials